Biophysical modelling of radiation effect - Chadwick, K. H. (Kenneth Helme), 1937-; Moschini, G; Varma, Matesh N ([Bristol, U.K. : Adam Hilger, 1992)
Proceedings of a workshop jointly organized by the Istituto Nazionale di Fisica Nucleare at Legnaro, Italy, the Office for Health and Environmental Research of the United States Department of Energy and the Commission of the European Communities, held in Padua, Italy, on 2-5 September 1991
Title from container
Title from title page on image in CD
Disalin daripada bahan mikrofis British Library (Sistem Pembekalan Penerbitan)
System requirements: Image viewer
Keywords: Radiation -- Physiological effect; Biophysics; Radiation -- Safety measures